2016
DOI: 10.1038/jid.2015.380
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein 3-Dependent Signaling Regulates Keratinocyte Migration and Wound Healing

Abstract: The desmosomal transmembrane adhesion molecules desmoglein 3 (Dsg3) and desmocollin 3 (Dsc3) are required for strong keratinocyte cohesion. Recently, we have shown that Dsg3 associates with p38MAPK and suppresses its activity. Here, we further investigated the role of Dsg3-dependent control of p38MAPK function. Dsg3-deficient mice display recurrent spontaneously healing skin erosions. In lesional and perilesional biopsies, p38MAPK activation was detectable compared to control animals. This led us to speculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 49 publications
2
61
1
Order By: Relevance
“…Thus, we suggest a novel pathway in which loss of Dsg2 triggers canonical MAPK signaling which in turn promotes migration due to reduced levels of PG. Because loss of cell‐cell cohesion by inducing a scratch wound is sufficient to activate pERK, it is conceivable that Dsg2 acts as a sensor for loss of adhesion in pancreatic cancer cells as it was proposed for Dsg3 in keratinocytes . In this model, Dsg2 by suppressing ERK activity keeps pancreatic cancer cells in an adhesive, quiescent state.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, we suggest a novel pathway in which loss of Dsg2 triggers canonical MAPK signaling which in turn promotes migration due to reduced levels of PG. Because loss of cell‐cell cohesion by inducing a scratch wound is sufficient to activate pERK, it is conceivable that Dsg2 acts as a sensor for loss of adhesion in pancreatic cancer cells as it was proposed for Dsg3 in keratinocytes . In this model, Dsg2 by suppressing ERK activity keeps pancreatic cancer cells in an adhesive, quiescent state.…”
Section: Discussionmentioning
confidence: 91%
“…Because loss of cell-cell cohesion by inducing a scratch wound is sufficient to activate pERK, it is conceivable that Dsg2 acts as a sensor for loss of adhesion in pancreatic cancer cells as it was proposed for Dsg3 in keratinocytes. 54 In this model, Dsg2 by suppressing ERK activity keeps pancreatic cancer cells in an adhesive, quiescent state. To our knowledge, no Dsg2 and only few PG variants were associated with epithelial cancers so far.…”
Section: Loss Of Plakoglobin Contributes To Increased Migrationmentioning
confidence: 99%
“…Wound‐healing migration assay : According to a published method with minor modification, 1×10 5 MDA‐MB‐231 cells were plated into 60 mm dishes for 48 h to achieve 80 % confluency. A wound on the confluent monolayer was created by scratching the monolayer with a yellow Gilson d200 pipette tip.…”
Section: Methodsmentioning
confidence: 99%
“…14,24 Further, some of the mice have an eye involvement, 14 which to our knowledge has not been characterized before. In our study, approximately half (43%) of Dsg3 KO mice showed eye symptoms during the observation period, such as reddened conjunctiva, small bleedings at the inner corner of the eye, and clotted eyelids ( Fig.…”
Section: Dsg3 Ko Mice Develop Conjunctival Disruptionmentioning
confidence: 92%
“…4A, 4B; arrows). We previously observed p38MAPK activation in the skin of Dsg3 KO animals 24 and, thus, investigated the activation of p38MAPK and MK2 in eyes of Dsg3 WT and KO mice. Activation of p38MAPK and less pronounced of MK2 was observed in Dsg3 KO animals, whereas no change of the total protein expression was detectable (Fig.…”
Section: Pv-igg Induces P38mapk Signaling and Depletion Of Dsg3 And Dmentioning
confidence: 99%